Resubmission of interim payment application no. 012 (Rev.1) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding resubmission of interim payment application no. 012 (Rev.1) of BRAC University new campus project.